THE USE OF RUNNING DICTATION IN TEACHING LISTENING SKILL AT THE SIXTH SEMESTER OF COKROAMINOTO PALOPO - Islamiah Yunus Yusrini Reski; Musfirah Musfirah (Institut Agama Islam Negeri Palopo, 2019)
This study aims at finding out whether Running Dictation Method is effective in teaching listening skill at the sixth semester of Cokroaminoto Palopo University. This study is pre-experimental design which consists of pre-test, treatment and post-test. The population of this study is the sixth semester of Cokroaminoto Palopo University. The technique used to select the sample is simple random sampling. The data analyzes using significant t-test (paired sample t-test). The result of the study shows that the value of mean score of pre-test (66.13) is lower than the mean score of post-test (75.90). it means that the use of Running Dictation is effective in teaching listening. The result of paired sample t-test shows that the value of sig. (2-tailed) is lower than alpha (α) (0.00<0.05), It means that Null Hypothesis (H0) is rejected and Alternative Hypothesis (H1) is accepted. Therefore Running Dictation Method is significantly effective in teaching listening at the sixth semester of Cokroaminoto Palopo university.